Improving of Tahsin Al-Qur’an for Children - Muhammad Amirudin; Imam Tabroni (PT FORMOSA CENDEKIA GLOBAL, 2022)
This research is motivated by the number of children who have not been the qur’an properly and correctly. This study aims to determine how to objective conditions of the ability to read Al-Qur’an at children in RW 03, and to be able to find how to application of tahsin in improving the ability to read Al-Qur’an at children in RW 03. Data analysis uses descriptive qualitative analysis with a mix method approach with a participatory action research design (PAR). The data collection technique is through interview, observation, and documentation. Based on the results of the study it was found that increasing of Al-Qur’an at the children in RW 03 environment is by providing understanding and practicing material about tahsin including the law of tajwid, makhorijul latter and how to read the Al-Qur’an properly and correctly (Tartil). The conclusion from the implementation of tahsin improvement activities on children has a significant effect on ability to read Al-Qur’an at children in the RW 03 environment. Supporting factors for the implementation of tahsin improvement carried out on children, namely the existance of supporting facilities and infrastructure such as a tahsin guide book fot teachers which has an influence on the ability to read Al-Qur’an.